CD133+-Derived Exosomes Carrying EIF3B Mediate Cell Metastasis and Stemness in Colorectal Cancer - Liao, Xiangwei; Han, Xiaodong; Wang, Yu; Yan, Jun; Wu, Zhenqian (Current Cancer Drug Targets, 2025)
<span class=
Keywords: EIF3B